2022
DOI: 10.3390/nu14214688
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of the Gut–Brain Axis through Metabolomics Identifies Serum Propionic Acid Associated with Higher Cognitive Decline in Older Persons

Abstract: The gut microbiome is involved in nutrient metabolism and produces metabolites that, via the gut–brain axis, signal to the brain and influence cognition. Human studies have so far had limited success in identifying early metabolic alterations linked to cognitive aging, likely due to limitations in metabolite coverage or follow-ups. Older persons from the Three-City population-based cohort who had not been diagnosed with dementia at the time of blood sampling were included, and repeated measures of cognition ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 73 publications
1
15
0
Order By: Relevance
“…Although it was initially designed for MS-based metabolomics, it should be noted that QC omics can also be used to manage other omics and MS data. In this sense, we would like to stress that some features of this QC protocol have successfully been applied in recent metabolomics and metallomics studies, which highlights its reliability to deal with complex and heterogeneous data. Therefore, we strongly believe that QC omics will facilitate the implementation of good QC practices, at both application and reporting levels, and thus become a gold standard in metabolomics research.…”
Section: Discussionmentioning
confidence: 99%
“…Although it was initially designed for MS-based metabolomics, it should be noted that QC omics can also be used to manage other omics and MS data. In this sense, we would like to stress that some features of this QC protocol have successfully been applied in recent metabolomics and metallomics studies, which highlights its reliability to deal with complex and heterogeneous data. Therefore, we strongly believe that QC omics will facilitate the implementation of good QC practices, at both application and reporting levels, and thus become a gold standard in metabolomics research.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of the tested drug compounds in this study on SCFAs production was variable and mostly independent of their effect on bacterial growth, in contrast to earlier studies’ results that a change in abundance of gut bacteria owing to drug usage was correlated to a similar effect on SCFAs production ( Hojo et al., 2018 ). Notably, numerous studies reveal that Bacteroidetes are the main producers of propionate in the human gut ( Salonen et al., 2014 ; Aguirre et al., 2016 ) and this SCFA is known for its ability to suppress inflammation and the increase in its level is associated with cognitive decline in elderly ( Kawasoe et al., 2022 ; Neuffer et al., 2022 ) while low level of propionic acid and acetate was linked to autism( Tetel et al., 2018 ). Progesterone and L-thryoxine reduced the production of propionic acid by B. fragilis .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, preclinical models have shown that modulation of neuroinflammation and cognitive decline can be achieved through oral supplementation with butyrate ( Govindarajan et al, 2011 ; Matt et al, 2018 ), however, these findings have yet to be explored in humans. In contrast, a population-based cohort in France with over 9,000 community dwellers aged 65 years or more, found that increased propionic acid in serum was associated with increased odds of cognitive decline ( Neuffer et al, 2022 ). Mediation analyses suggested that this adverse association may be mediated through hypercholesterolemia and glycaemia with a strong correlation with a fasting blood glucose suggesting metabolic disruption as a possible pathway in relation of propionic acid to cognitive health ( Neuffer et al, 2022 ).…”
Section: Strategies For Targeting the Gut Microbiome For Better Brain...mentioning
confidence: 98%
“…In contrast, a population-based cohort in France with over 9,000 community dwellers aged 65 years or more, found that increased propionic acid in serum was associated with increased odds of cognitive decline ( Neuffer et al, 2022 ). Mediation analyses suggested that this adverse association may be mediated through hypercholesterolemia and glycaemia with a strong correlation with a fasting blood glucose suggesting metabolic disruption as a possible pathway in relation of propionic acid to cognitive health ( Neuffer et al, 2022 ). Overall these data suggests that the effect of microbial metabolites are context-dependent where further research is needed to understand how underlying conditions can prevent or perturbate the effects of microbial metabolites.…”
Section: Strategies For Targeting the Gut Microbiome For Better Brain...mentioning
confidence: 98%